ASSESMENT OF BUTTERFLY SPECIES AND RELETIVE ABUNDANCE IN AREA OF GHOT TAHASIL CHAMORSHI DISTRICTGADCHIROLI (M.S.) INDIA - Sapana M. Deshmukh; Telkhade Pravin Madhukarrao (The Bioscan, 2025)
The present study on species diversity and distribution of butterfly was carried out at GhotTahasil ChamorshiDist.Gadchiroli (M.S.).All of the environmental conditions played a significant role in determining the butterfly diversity and density. They are good indicators of climatic, atmospheric and seasonal ecological changes. Being a cold blooded invertebrate’s butterflies is easily shows significant impact by climatic changes. Present investigation carried out for two year during Jan 2023to Dec 2024 at rural area of Ghot.In present investigation, total 60 species were recorded and identified among these include in five Families Nymphalidae with 28 species followed by Pieridae with 10 species and family Papilionidae with 09 species family Lycaenidae with 08 species and family Hesperidae with 05 species.Most of the butterfly species were very commonly called as Brush-footed butterflies followed by Papilionidae commonly called as Swallowtails species and Pierdae commonly called as white and Yellows species.Abundance and biodiversity of butterfly depends on climate change. As per the literature its indicate that all butterflies species has its significant importance in balancing biodiversity of ecosystem so in view of the study need of future planning,climate impact and conservation of host plants and also focus on the current status of diversity and abundance of butterflies in Ghot area near ChamorshiDistrictGadchiroli (M.S.) India.